Respuesta :

The inverse of this function would be f(x) = [tex] \frac{Log(x - 6)}{Log2} [/tex].



You can find the value of any inverse function by switching the f(x) and the x value. Then you can solve for the new f(x) value. The end result will be your new inverse function. The step-by-step process is below.



f(x) = [tex] 2^{x} [/tex] - 6 ----> Switch f(x) and x



x = [tex] 2^{f(x)} [/tex] - 6 ----> Add 6 to both sides



x + 6 = [tex] 2^{f(x)} [/tex] -----> Take the logarithm of both sides in order to get the f(x) out of the exponent



Log(x + 6) = f(x)Log2 ----> Now divide both sides by Log2



[tex] \frac{Log(x + 6)}{Log2} [/tex] = f(x) ----> And switch the order for formatting purposes.



f(x) = [tex] \frac{Log(x + 6)}{Log2} [/tex]



And that would be your new inverse function.

Answer:

f^-1 (x) = log 2 (x-6)

Step-by-step explanation: